2021
DOI: 10.1249/jsr.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Risk Factors, and Nonsurgical Treatment of Injuries Related to Endurance Running

Abstract: Running is a popular form of exercise that is easily accessible to various populations; endurance running, defined as distances beyond 5 km, continues to grow within the sport. Endurance running-related injuries are common in the lower extremities and are primarily overuse related. A multitude of risk factors for injury exist, including extrinsic factors, such as running distance and frequency, and intrinsic factors, such as biomechanics and nutrition status. Training and rehabilitation techniques vary with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Studies have shown that during the running cycle, the tibia is impacted, and the knee exion angle increases at the moment of foot strike and during the off-ground phase of each run. When muscles are subjected to prolonged repetitive loading, the strength of the hamstrings and quadriceps decreases, leading to increased tibial inversion rotation, femoral translation, and increased risk of KOA [30][31][32] . Another important cause of KOA may be changes in knee cartilage caused by prolonged loading.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that during the running cycle, the tibia is impacted, and the knee exion angle increases at the moment of foot strike and during the off-ground phase of each run. When muscles are subjected to prolonged repetitive loading, the strength of the hamstrings and quadriceps decreases, leading to increased tibial inversion rotation, femoral translation, and increased risk of KOA [30][31][32] . Another important cause of KOA may be changes in knee cartilage caused by prolonged loading.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown frontal and transverse plane motion at the foot is associated with AT (9,22,33); the biomechanical model utilized for this study includes a 1 degree-of-freedom ankle joint, which limited our ability to assess nonsagittal planes of motion about the foot and ankle. There are many variables thought to influence running-related injury risk, such as training habits (34,35), nutritional characteristics (36,37), and mental health (38,39). As the magnitude of differences observed in this study is relatively small, these differences may partially reflect measurement error for these variables (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the immunity system, another health concern of marathon runners was the occurrence of musculoskeletal injuries. Marathon runners were subject to injuries, mostly in the lower limbs, related to overuse ( 24 ). Ashcroft ( 25 ) highlighted the role of adequate sleep in the context of the prevention of injuries in distance runners.…”
Section: Sleep In Marathon and Ultramarathon Runnersmentioning
confidence: 99%